Global disease burden: use in health planning in the State of Rio Grande do Sul (Research, Society and Development, 2020)
The objective of this article is to present the experience and the results of adopting the Global Burden of Disease (CGD) approach in Health Planning in the State of Rio Grande do Sul (RS), Brazil, specifically for the 2020-2023 Health Plan. Methodology: The CGD is calculated with secondary data and population studies and it shows health loss due to diseases, injuries and risk factors by age, sex, year and place. Our source was the data available in the Institute for Health Metrics and Evaluation website, from the University of Washington. We developed a descriptive analysis of the RS data for the Health Plan. Results: Analyzing the Global Burden of Disease of the State of RS by Disability Adjusted Life Years (DALYs) from 1990 to 2017, we noticed an increase in chronic conditions. Despite the contributions of the approach, some challenges were identified, such as the difficulty of understanding of this content by non-specialists and the need to let the information available by Brazilian Health Regions. Conclusions: The potential of adopting the Global Burden of Disease is pointed out to identify possible paths for health planning and decision-making, as well as the challenge for SUS management to translate, in the priority goals of the planning and management instruments, the health demands identified from the GCD.